(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The Latium Region in Italy is currently under pressure from national government to achieve economic consolidation of regional health services and is subject to a formal regional recovery plan. Methods: Using recognized health indicators together with a government assessment tool, we evaluate the impact of the economic downturn on the health of the Latium Region population. Results: We find that healthcare spending in the Latium Region needs to become more efficient by improving primary healthcare and by restoring efficiency in hospitals. Conclusions: Prevention activities should not only be defended in the current financial and economic crisis, but also streamlined and strengthened.